Isoprinosine augmentation of phytohemagglutinin-induced lymphocyte proliferation. - Hadden, J W (1976)
The need for agents designed to modify immune response in the treatment of patients with viral infection, immunodeficiency, or cancer prompted the present study on the mechanisms of action of isoprinosine, a compound developed for antiviral use and whose therapeutic activity may involve the immune system. The effect of isoprinosine on in vitro proliferation of human peripheral blood lymphocytes stimulated by phytohemagglutinin (PHA) and on lymphocyte levels of cyclic adenosine 3',5'-monophosphate and cyclic guanosine 3',5'-monophosphate was analyzed. Over a concentration range from 0.2 to 250 mug/ml, isoprinosine augmented PHA-induced proliferation; maximal stimulation was observed between 25 to 50 mug/ml. Isoprinosine in the absence of PHA had no effect on proliferation. The relative lack of effect of isoprinosine during a 90-min exposure and the lack of effect on lymphocyte cyclic nucleotide levels indicate that isoprinosine potentiates the PHA response by a mechanism different than a number of hormonal agents and such immunopotentiators as levamisole, polyadenylic-acid, and endotoxin. Further evaluation of isoprinosine as an immunopotentiator is indicated.